2016
DOI: 10.1177/0022042616678610
|View full text |Cite
|
Sign up to set email alerts
|

African American Women and Sexually Transmitted Infections: The Contextual Influence of Unbalanced Sex Ratios and Individual Risk Behaviors

Abstract: This study uses data from 564 African American women to examine the correlates of lifetime prevalence of a sexually transmitted infection (STI). Specifically, we test the effects of perceptions about the availability of African American males, five partner characteristics, and drug history. At the bivariate-level, women with an STI diagnosis were significantly more likely to have dated a man who was married, older, had sex with another man, involved in concurrent partnerships, and had been incarcerated. About … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…However, considering the importance of relationships, traditional gender roles, and close knit social networks in the Appalachian culture, it is feasible that more male sex partners may be a contributing factor in the relationship between drug use and crime among rural women. In addition, living in disadvantaged areas, particularly if the number of healthy and desirable partners is limited, has been associated with high-risk sexual practices (Ramaswamy & Kelly, 2015; Oser et al, 2016). While the significance of the interaction in this study may suggest that sexual activity with more partners contributes to drug use and crime among rural women, the complexity of drug use and high-risk sexual practices should be assessed in criminal justice venues more broadly for both rural and urban women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, considering the importance of relationships, traditional gender roles, and close knit social networks in the Appalachian culture, it is feasible that more male sex partners may be a contributing factor in the relationship between drug use and crime among rural women. In addition, living in disadvantaged areas, particularly if the number of healthy and desirable partners is limited, has been associated with high-risk sexual practices (Ramaswamy & Kelly, 2015; Oser et al, 2016). While the significance of the interaction in this study may suggest that sexual activity with more partners contributes to drug use and crime among rural women, the complexity of drug use and high-risk sexual practices should be assessed in criminal justice venues more broadly for both rural and urban women.…”
Section: Discussionmentioning
confidence: 99%
“…For example, due to low population density, rural women may have limited mobility and anonymity (Friedman, 2003), suggesting that a high-risk home environment where family members or peers use drugs may present challenges for rural women to “escape”. Additionally, based on findings from studies on partner availability analysis in other cultural groups of women (Oser et al, 2016), it is possible that the availability of partners who are not engaged in drug use and criminal activity are limited for rural women drug-users in Appalachia. Thus, high-risk partners may increase the likelihood of rural women engaging in high-risk behaviors.…”
Section: Examining the Drug/crime Relationship Among Rural Womenmentioning
confidence: 99%
“…Compared to incarcerated men, women who are incarcerated have a significantly higher prevalence of all medical and psychiatric conditions (Binswanger et al, ; Maruschak, Berzofsky, & Unangst, ). Black women (including those with incarceration history) are also at high risk of getting a sexually transmitted disease, which often results from dating men who have concurrent sexual partnerships or had been incarcerated (Oser et al, ). In addition, 80% of incarcerated women are mothers and about 5% are pregnant when they are incarcerated (McCampbell, ; Swavola et al, ).…”
Section: Social Determinants Of Health and Mass Incarcerationmentioning
confidence: 99%
“…Throughout college campuses in particular, research has demonstrated various individual (e.g., low risk perception), social (e.g., power disparities, sexual double standards), and structural factors (e.g., limitations in Black women's choices of partners due to the lesser numbers of low-risk (willing to be monogamous or preference for bi-sexual relationships) Black males for romantic and/or sexual partnerships on college campuses), which effects Black college women's HIV risk [2,17,29,30]. The interplay between these factors may result in Black college women being more likely to engage in behaviors that unknowingly place them at greater risk for HIV and STI acquisition [2,29]. A study conducted by the Center for Disease Control and Prevention (CDC) demonstrated that students attending HBCUs serve as a potential bridge for HIV transmission between high-and low-risk populations [31].…”
Section: Sexual Health Concerns Of Black Women On College Campusesmentioning
confidence: 99%
“…Despite this progress however, a disproportionate number of new HIV infections continue to occur among Black women. Additionally, Black women as a subgroup have a higher rate of HIV and sexually transmitted infections (STIs) compared with any other female group in the USA [2,3]. In 2017, Black women accounted for 60% of newly diagnosed HIV infections among women in the U.S. [4,5].…”
Section: Introductionmentioning
confidence: 99%